The Importance of the Network in International Music Competitions - Pilkytė, Rūta (Vilnius University Open Series, 2021)
Collaboration between art organisations from different fields and countries is not a new phenomenon. However, the networking of art institutions is of a more recent nature. In Lithuania, international music competitions are organised by a non-governmental public institution “Natų knygynas”. This institution holds membership in different international organisations like the European Union of Music Competitions for Youth (EMCY) and the World Federation of International Music Competitions (WFIMC). The purpose of this report is to study the characteristics of EMCY and WFIMC international networks by applying comparative analysis of scientific literature and analysis of primary and secondary documents. The article presents the benefits of networking for international music competitions in Lithuania.